Composition, nickel electrode base band and nickel positive electrode battery

By using a composition composed of nickel, pore-forming agent, sodium carboxymethylcellulose and methylcellulose, a nickel electrode baseband with a thickness of more than 1.2 mm and a good appearance, the problems of insufficient thickness and appearance cracks in the prior art are solved.

CN119890304APending Publication Date: 2025-04-25JIANGSU HIGHSTAR BATTERY MFG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311375427.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The thickness of the existing nickel electrode baseband can only reach less than 1.1 mm, and there is a problem of appearance cracks.

Method used

A nickel electrode baseband formed by drying and sintering is used to form a composition consisting of nickel, a pore-forming agent, binder 1 (sodium carboxymethylcellulose) and binder 2 (methylcellulose).

Benefits of technology

The thickness of the nickel electrode baseband is achieved above 1.2mm and maintains good appearance quality, solving the problems of insufficient thickness and appearance cracks.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of nickel anode batteries, and discloses a composition, a nickel electrode base band and a nickel anode battery. The composition comprises nickel, a pore-forming agent, a binder 1 and a binder 2, wherein the binder 1 is sodium carboxymethyl cellulose, and the binder 2 is methyl cellulose. The binder 1 and the binder 2 are combined to be used as the binder, so that not only can the adhesion amount of the prepared slurry be increased when the prepared slurry passes through a larger scraper gap, but also the phenomena of slurry sagging, cracking and the like caused by temperature rise in the drying process can be avoided, so that a thicker nickel electrode base band can be obtained, and a good appearance can be kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nickel anode batteries, and in particular to a composition, a nickel electrode base strip and a nickel positive electrode battery. Background Art

[0002] Alkaline batteries (nickel-cadmium batteries, nickel-metal hydride batteries, nickel-iron batteries, nickel-zinc batteries, etc.) with nickel electrodes as positive electrodes are widely used chemical power sources with good charge and discharge performance, high energy density and low internal resistance. In recent years, due to the impact of lithium-ion batteries, its application field has been greatly reduced, but due to its good safety and reliability, it still has broad application prospects in the fields of railways, energy storage, UPS power supplies, etc. Nickel electrodes are divided into foamed nickel scraper-type nickel electrodes, bag-type nickel electrodes and sintered nickel positive electrodes according to the process. Although the foamed nickel scraper-type positive electrode and bag-type positive electrode have high capacity density and low price, the electrode powder of this type of battery is easy to fall off during long-term charging and discharging, which is prone to hidden dangers such as micro-short circuits. Although the price of sintered nickel positive electrode batteries is relatively high, they are favored in the fields of railways, energy storage, etc. because of their excellent strength, high power, long life, high safety and other characteristics. Reducing the manufacturing cost of sintered nickel batteries is the key to improving the competitiveness of nickel batteries. Sintered nickel electrodes are key components of sintered nickel batteries. Increasing the thickness of sintered nickel electrodes can not only increase the capacity of the electrodes, but also reduce the material consumption of battery separators, base strips, etc., thereby reducing battery manufacturing costs. However, the current technological level can only achieve a thickness of 1.0-1.1mm for sintered nickel positive electrodes, and sintered nickel electrodes with a thickness greater than 1.1 have not yet been reported. During production, it was found that due to slurry problems, sizing was difficult, and only a base strip with a thickness of less than 1.1mm could be achieved, and there were problems such as appearance cracks.

[0003] Therefore, there is an urgent need for a nickel electrode base strip with a thickness of more than 1.1 mm and no cracks in appearance. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the nickel electrode base strip in the prior art can only reach a thickness of less than 1.1 mm and has cracks in appearance, and to provide a composition, a nickel electrode base strip and a nickel positive electrode battery. The slurry formed by the composition is coated on the surface of the substrate, and the nickel electrode base strip obtained by drying and sintering has a thickness of more than 1.1 mm and has no cracks in appearance.

[0005] In order to achieve the above object, the first aspect of the present invention provides a composition, wherein the composition comprises: nickel, a pore former, a binder 1 and a binder 2; wherein,

[0006] The binder 1 is sodium carboxymethyl cellulose, and the binder 2 is methyl cellulose.

[0007] The second aspect of the present invention provides a nickel electrode substrate, wherein the nickel electrode substrate is obtained by coating the composition provided by the present invention on at least one surface of a substrate, followed by drying and sintering.

[0008] A third aspect of the present invention provides a nickel positive electrode battery, wherein the nickel positive electrode battery comprises a nickel positive electrode, and the nickel positive electrode is made of the nickel electrode substrate provided by the invention.

[0009] The fourth aspect of the present invention provides an application of a pore former, a binder 1 and a binder 2 in improving the thickness and surface quality of a nickel electrode base strip; wherein:

[0010] The binder 1 is sodium carboxymethyl cellulose, and the binder 2 is methyl cellulose.

[0011] Through the above technical solution, the beneficial effects of the present invention are:

[0012] The present invention adopts the combination of binder 1 and binder 2, which can not only increase the adhesion amount of the slurry when the slurry passes through a larger scraper gap, but also prevent the slurry from sagging and cracking due to the increase in temperature during the drying process, so that a nickel electrode base strip with a thickness of more than 1.2 mm can be obtained while maintaining a good appearance. The problem of cracking and thickness not meeting the requirements in the production of ultra-thick nickel electrode base strips is solved, creating conditions for increasing electrode capacity, reducing battery volume, and reducing battery capacity costs.

[0013] In a preferred embodiment of the present invention, in the preparation of the slurry for preparing the nickel electrode base band, the binder 1 and the binder 2, the nickel powder and the pore-forming agent are first mixed by a V-shaped mixer, and further dispersed by vibration screening, so that the powders are fully mixed and dispersed evenly, avoiding the agglomeration of the powders, and making the slurry prepared subsequently more uniform. The present invention adopts a vacuum feeding method under stirring when adding slurry, which can make the powder more easily dispersed evenly in the solvent and avoid the generation of dry powder particles in the slurry. In addition, the present invention further improves the thickness of the nickel electrode base band by selecting the appropriate amount of each component in the powder, the amount of solvent, and the types of sodium carboxymethyl cellulose and methyl cellulose; by selecting a suitable pore-forming agent, the pore-forming agent, nickel, sodium carboxymethyl cellulose and methyl cellulose play a good synergistic role, which not only further improves the thickness of the nickel electrode base band, but also further improves the porosity of the nickel electrode base band. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] The first aspect of the present invention provides a composition, wherein the composition comprises: nickel, a pore former, a binder 1 and a binder 2; wherein,

[0016] The binder 1 is sodium carboxymethyl cellulose, and the binder 2 is methyl cellulose.

[0017] The present invention uses a combination of binder 1 and binder 2 as a binder, which can not only increase the adhesion amount of the prepared slurry when passing through a larger scraper gap, but also prevent the slurry from sagging, cracking, etc. due to the increase in temperature during the drying process. In this way, a nickel electrode base strip with a thickness of more than 1.2 mm can be obtained while maintaining a good appearance.

[0018] According to the present invention, preferably, in the composition, the weight ratio of the binder 1 to the binder 2 is (0.5-5.1):1.

[0019] According to the present invention, preferably, based on the total weight of the nickel, the pore former, the binder 1 and the binder 2, the contents of the binder 1 and the binder 2 are 0.9-2.6wt% and 0.5-1.5wt%, respectively.

[0020] According to the present invention, preferably, in the composition, the weight ratio of the nickel to the pore-forming agent is (7-27):1.

[0021] According to the present invention, preferably, based on the total weight of the nickel, the pore former, the binder 1 and the binder 2, the contents of the nickel and the pore former are 85-95wt% and 3.6-15wt%, respectively.

[0022] In order to further increase the thickness of the prepared nickel electrode base tape and further improve the appearance quality of the nickel electrode base tape, preferably, the viscosity of the 1 wt % aqueous solution of sodium carboxymethyl cellulose at 25° C. is greater than or equal to 500 mPa·s.

[0023] In order to further increase the thickness of the nickel electrode substrate and further improve the appearance quality of the nickel electrode substrate, preferably, the viscosity of the 1wt% aqueous solution of the methyl cellulose at 25° C. is 400-600mPa·s. For example, methyl cellulose of brand MH4000 can be selected.

[0024] The combined use of sodium carboxymethyl cellulose and methyl cellulose that meet the above conditions can ensure that the slurry has a suitable viscosity, so that the base tape has a uniform thickness and does not crack when dried, further improving the appearance quality of the nickel electrode base tape.

[0025] According to the present invention, preferably, the average particle size of the nickel is 2.1-2.8 μm, and the bulk density is 0.5-0.65 g / cm 3 The average particle size and bulk density of nickel satisfy this range, which can further improve the porosity of the nickel electrode substrate, and the pore size distribution of the substrate is more uniform, which is beneficial to subsequent impregnation and improving the performance of the nickel electrode.

[0026] According to the present invention, preferably, the pore-forming agent is selected from polyvinyl butyral (PVB) and / or ammonium bicarbonate, preferably polyvinyl butyral. Using polyvinyl butyral as a pore-forming agent can play a good synergistic role with nickel, sodium carboxymethyl cellulose and methyl cellulose, and the obtained nickel electrode base tape has not only a greater thickness, but also a higher porosity.

[0027] Preferably, the average particle size of the polyvinyl butyral is 100-500 μm.

[0028] Preferably, the viscosity of a 10 wt % ethanol solution of the polyvinyl butyral at 25° C. is 5-10 mPa·s.

[0029] In order to make the viscosity of the slurry formed by nickel, pore former, binder 1, binder 2 and solvent suitable for subsequent coating of the slurry on the substrate surface, preferably, the composition also contains a solvent. After adding the solvent, a slurry for preparing a nickel electrode base tape is formed.

[0030] According to the present invention, preferably, the solvent is water.

[0031] According to the present invention, preferably, the solvent is water with an electrical conductivity less than or equal to 6.67 μS.

[0032] In order to make the slurry have a suitable viscosity, thereby making the base tape thickness more uniform and further improving the appearance quality of the nickel electrode base tape, preferably, the solvent content in the composition is 50-60wt%, that is, the solid content in the slurry is 40-50wt%.

[0033] In the present invention, the above raw materials can be directly mixed to obtain the composition of the present invention. According to one embodiment of the present invention, the preparation method of the slurry for preparing the nickel electrode base tape includes: mixing nickel, a pore former, a binder 1, a binder 2 and a solvent to obtain the slurry. In order to make the raw materials mixed more uniformly, thereby further improving the performance of the obtained nickel positive electrode battery, when preparing the slurry, nickel, a pore former, a binder 1 and a binder 2 are first mixed to obtain a powder, and then the powder and the solvent are mixed to obtain a slurry.

[0034] According to the present invention, there is no special requirement for the mixing conditions. Preferably, the conditions for mixing the powder and the solvent include: mixing the powder and the solvent in a vacuum environment, the mixing temperature is 50-70° C., and the mixing time is 1.5-3 h.

[0035] According to a preferred embodiment of the present invention, nickel, pore-forming agent, sodium carboxymethyl cellulose and methyl cellulose are first mixed by a V-shaped mixer (e.g., 20-40 minutes) to fully mix the powders, and then further dispersed by vibrating sieving with a mesh of 60-100, and then the mixed powders are added to a slurry mixer containing a solvent by vacuum feeding under stirring, and stirred under vacuum (e.g., 1.5-3 hours) to obtain a slurry for preparing a nickel electrode base band. Nickel, pore-forming agent, sodium carboxymethyl cellulose and methyl cellulose are first mixed by a V-shaped mixer, and then dispersed by vibrating sieving to mix and disperse the powders evenly, thereby avoiding agglomeration of the powders and making the slurry prepared subsequently more uniform. Vacuum feeding under stirring can make the powders more easily dispersed evenly in the solvent and avoid the generation of dry powder particles in the slurry.

[0036] According to a more preferred embodiment of the present invention, the preparation method of the slurry for preparing the nickel electrode base tape comprises the following steps: firstly, nickel (average particle size of 2.1-2.8 μm, bulk density of 0.5-0.65 g / cm 3), polyvinyl butyral (average particle size of 100-500 μm, viscosity of 10 wt% ethanol solution at 25°C is 5-10 mPa·s), sodium carboxymethyl cellulose (viscosity of 1 wt% aqueous solution at 25°C is greater than or equal to 500 mPa·s) and methyl cellulose (viscosity of 1 wt% aqueous solution at 25°C is 400-600 mPa·s) are mixed in a V-shaped mixer for 20-40 minutes to fully mix the powders, and then a 60-100 mesh The powder is dispersed by vibrating and sieving to obtain a powder (the contents of nickel, polyvinyl butyral, sodium carboxymethyl cellulose and methyl cellulose in the powder are 85-95wt%, 3.6-15wt%, 0.9-2.6wt% and 0.5-1.5wt% respectively); then the powder is added to a pulping machine containing water (the conductivity of the water is less than or equal to 6.67μS and the temperature of the water is 50-70℃) by vacuum feeding under stirring, and stirred in a vacuum environment for 1.5-3h to obtain a slurry. The amount of water in the slurry is 50-60wt%.

[0037] The second aspect of the present invention provides a nickel electrode substrate, wherein the nickel electrode substrate is obtained by coating the composition provided by the present invention on at least one surface of a substrate, followed by drying and sintering.

[0038] According to the present invention, the substrate may be a substrate commonly used in the art for preparing nickel electrode base strips. Preferably, the substrate is a nickel-plated steel strip.

[0039] According to the present invention, there is no particular requirement for the drying conditions or methods, as long as most of the solvent can be removed. For example, the drying conditions may include: a temperature of 160-180° C.; and a time of 15-45 min.

[0040] According to the present invention, preferably, the sintering is carried out in the presence of a protective gas and H2, and the presence of H2 can prevent the nickel electrode substrate from being oxidized during the sintering process. The protective gas can be selected from nitrogen and / or an inert gas (such as helium and argon), preferably nitrogen. When nitrogen is used as the protective gas, the volume ratio of nitrogen and H2 can be (1.5-2):1.

[0041] According to the present invention, preferably, the sintering temperature is 900-1000° C. and the sintering time is 5-30 min.

[0042] According to a preferred embodiment of the present invention, the preparation method of the nickel electrode base strip comprises the following steps: in a vertical scraping device, the slurry is coated on a punched nickel-plated steel strip and dried, the coating speed is 35-50m / h, and the drying temperature is 160-180°C; then sintering is carried out in a sintering furnace in the presence of nitrogen and hydrogen, the sintering temperature is 900-1000°C, and the sintering time is 5-30min to obtain the nickel electrode base strip.

[0043] The thickness of the nickel electrode substrate obtained according to the preferred implementation method of the present invention can be greater than or equal to 1.2 mm, and the porosity is greater than 80%.

[0044] The third aspect of the present invention provides a nickel positive electrode battery, wherein the nickel positive electrode battery comprises a nickel positive electrode, and the nickel positive electrode is made from the nickel electrode substrate provided by the present invention. The nickel positive electrode is obtained by chemically impregnating or electrochemically impregnating the nickel electrode substrate in a nickel nitrate solution, and then alkalizing, washing, and the like. The nickel positive electrode battery also includes a sintered cadmium negative electrode (or a bonded cadmium negative electrode), a diaphragm, and an electrolyte.

[0045] A fourth aspect of the present invention provides an application of an adhesive 1 and an adhesive 2 in improving the thickness and surface quality of a nickel electrode substrate; wherein:

[0046] The specific types and proportions of the adhesive 1 and the adhesive 2 are described above and will not be repeated here.

[0047] The present invention uses a combination of binder 1 and binder 2 as a binder, which can not only increase the adhesion amount of the prepared slurry when passing through a larger scraper gap, but also prevent the slurry from sagging, cracking, etc. due to the increase in temperature during the drying process. In this way, a nickel electrode base strip with a thickness of more than 1.2 mm can be obtained while maintaining a good appearance.

[0048] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, all methods are conventional methods; and the reagents and materials used, unless otherwise specified, can be obtained from commercial sources.

[0049] The following examples illustrate the preparation of slurries and nickel electrode substrates.

[0050] Example 1

[0051] The preparation method of the slurry is as follows:

[0052] First, nickel (average particle size 2.3μm, bulk density 0.6g / cm 3), polyvinyl butyral (average particle size of 180 μm, viscosity of 10wt% ethanol solution at 25°C is 8 mPa·s), sodium carboxymethyl cellulose (viscosity of 1wt% aqueous solution at 25°C is 550 mPa·s) and methyl cellulose (viscosity of 1wt% aqueous solution at 25°C is 500 mPa·s) are mixed in a V-shaped mixer for 30 min to fully mix the powders, and then dispersed through a 60-mesh vibration sieve to obtain a powder (the contents of nickel, polyvinyl butyral, sodium carboxymethyl cellulose and methyl cellulose in the powder are 91.5wt%, 5wt%, 2.6wt% and 0.9wt%, respectively); then the powder is added into a pulping machine filled with water (the conductivity of the water is 2μS, and the temperature of the water is 60°C) by vacuum feeding under stirring, and stirred for 2h in a vacuum environment with a pressure of -0.9MPa to obtain a slurry; the amount of water in the slurry is 56.8wt%.

[0053] The preparation method of the nickel electrode base tape is as follows:

[0054] In a vertical scraping device, the slurry is coated onto the surfaces of both sides of a punched nickel-plated steel strip and dried at a coating speed of 42 m / h, a drying temperature of 170°C, and a time of 30 min; then it is sintered in a sintering furnace in the presence of nitrogen and hydrogen (volume ratio of 1.8:1) at a sintering temperature of 960°C and a sintering time of 10 min to obtain a nickel electrode base strip.

[0055] Example 2

[0056] The preparation method of the slurry is as follows:

[0057] First, nickel (average particle size of 2.1 μm, bulk density of 0.6 g / cm 3 ), polyvinyl butyral (average particle size of 420 μm, viscosity of 10wt% ethanol solution at 25°C is 10 mPa·s), sodium carboxymethyl cellulose (viscosity of 1wt% aqueous solution at 25°C is 500 mPa·s) and methyl cellulose (viscosity of 1wt% aqueous solution at 25°C is 450 mPa·s) are mixed in a V-shaped mixer for 30 min to fully mix the powders, and then dispersed through a 60-mesh vibration sieve to obtain a powder (the contents of nickel, polyvinyl butyral, sodium carboxymethyl cellulose and methyl cellulose in the powder are 85wt%, 12wt%, 2wt% and 1wt%, respectively); then the powder is added into a pulping machine filled with water (the conductivity of the water is 1.8μS, and the temperature of the water is 60°C) by vacuum feeding under stirring, and stirred for 2h in a vacuum environment with a pressure of -0.9MPa to obtain a slurry; the amount of water in the slurry is 54.5wt%.

[0058] The preparation method of the nickel electrode base tape is the same as that of Example 1 to obtain the nickel electrode base tape.

[0059] Example 3

[0060] First, nickel (average particle size of 2.8 μm, bulk density of 0.54 g / cm 3 ), polyvinyl butyral (average particle size of 250 μm, viscosity of 10 wt% ethanol solution at 25°C of 5 mPa·s), sodium carboxymethyl cellulose (1 wt% aqueous solution viscosity at 25°C of 580 mPa·s) and methyl cellulose (1 wt% aqueous solution viscosity at 25°C of 510 mPa·s) were mixed in a V-shaped mixer for 30 min to fully mix the powders, and then dispersed through a 60-mesh vibration sieve to obtain a powder (the contents of nickel, polyvinyl butyral, sodium carboxymethyl cellulose and methyl cellulose in the powder were 94 wt%, 3.6 wt%, 0.9 wt% and 1.5 wt% respectively); then, the powders were added into a pulping machine containing water (the conductivity of the water was 3 μS and the temperature of the water was 60°C) by vacuum feeding under stirring, and stirred for 2 h in a vacuum environment with a pressure of -0.9 MPa to obtain a slurry; the amount of water in the slurry was 60 wt%. .

[0061] The preparation method of the nickel electrode base tape is the same as that of Example 1 to obtain the nickel electrode base tape.

[0062] Example 4

[0063] The slurry and the nickel electrode base tape were prepared according to the method of Example 1, except that the amount of sodium carboxymethyl cellulose and methyl cellulose was different. Specifically, the contents of nickel, polyvinyl butyral, sodium carboxymethyl cellulose and methyl cellulose in the powder were 91.5wt%, 5wt%, 3wt% and 0.5wt%, respectively. The slurry was obtained, and then the nickel electrode base tape was obtained. The amount of water in the slurry was 56.8wt%.

[0064] Example 5

[0065] The slurry and the nickel electrode base tape were prepared according to the method of Example 1, except that the amounts of nickel, polyvinyl butyral, sodium carboxymethyl cellulose and methyl cellulose were different. Specifically, the contents of nickel, polyvinyl butyral, sodium carboxymethyl cellulose and methyl cellulose in the powder were 88.5wt%, 4.8wt%, 5wt% and 1.7wt%, respectively. The slurry was obtained, and then the nickel electrode base tape was obtained. The amount of water in the slurry was 56.8wt%.

[0066] Example 6

[0067] The slurry and nickel electrode base tape were prepared according to the method of Example 1, except that the average particle size was 2 μm and the bulk density was 0.65 g / cm 3The average particle size of the nickel "replacement" is 2.3μm and the bulk density is 0.6g / cm 3 Nickel". A slurry is obtained, and then a nickel electrode base tape is obtained. The amount of water in the slurry is 56.8wt%.

[0068] Comparative Example 1

[0069] The slurry and the nickel electrode substrate were prepared according to the method of Example 1, except that the sodium carboxymethyl cellulose was replaced with an equal weight of methyl cellulose to obtain the slurry and then the nickel electrode substrate. The amount of water in the slurry was 56.8 wt%.

[0070] Comparative Example 2

[0071] The slurry and the nickel electrode substrate were prepared according to the method of Example 1, except that the methyl cellulose was replaced by an equal weight of sodium carboxymethyl cellulose to obtain the slurry and then obtain the nickel electrode substrate. The amount of water in the slurry was 56.8 wt%.

[0072] Comparative Example 3

[0073] The slurry and nickel electrode base tape were prepared according to the method of Example 1, except that sodium carboxymethylcellulose (1wt% aqueous solution with a viscosity of 550mPa·s at 25°C) was replaced with an equal weight of hydroxypropyl methylcellulose (1wt% aqueous solution with a viscosity of 510mPa·s at 25°C), and methylcellulose (1wt% aqueous solution with a viscosity of 500mPa·s at 25°C) was replaced with an equal weight of hydroxypropyl methylcellulose (1wt% aqueous solution with a viscosity of 510mPa·s at 25°C). Slurry was obtained, and then a nickel electrode base tape was obtained. The amount of water in the slurry was 56.8wt%.

[0074] Test Case

[0075] The thickness, porosity and cracking of the nickel electrode substrates prepared in each embodiment and comparative example were measured respectively. The porosity was measured by vacuum immersion method, the substrate thickness was measured by a screw micrometer with an accuracy of 0.01 mm or more, and the cracking was measured by visual inspection. The results are shown in Table 1.

[0076] Table 1

[0077] serial number Thickness, mm Porosity, % Nickel electrode base strip appearance Example 1 1.25 82.1 No cracks on the surface Example 2 1.21 83 No cracks on the surface Example 3 1.23 80.5 No cracks on the surface Example 4 1.2 81 No cracks on the surface Example 5 1.2 80.5 No cracks on the surface Example 6 1.21 80.6 No cracks on the surface Comparative Example 1 1.05 81.3 Surface cracks Comparative Example 2 1.12 80.5 Large cracks on the surface Comparative Example 3 0.97 79.3 Surface cracks

[0078] From the results in Table 1, it can be seen that the thickness of the nickel electrode base tape obtained in Examples 1-6 is above 1.2 mm, and the porosity is above 80%, and the appearance is good without cracks. In Comparative Example 1, sodium carboxymethyl cellulose is replaced by an equal weight of methyl cellulose, and in Comparative Example 2, methyl cellulose is replaced by an equal weight of sodium carboxymethyl cellulose. In both Comparative Example 1 and Comparative Example 2, only one of methyl cellulose and sodium carboxymethyl cellulose is added, instead of using a combination of two binders. Compared with Examples 1-6, the thickness of the nickel electrode base tape obtained in Comparative Example 1 and Comparative Example 2 is less than 1.2 mm, and there are cracks on the surface. Comparative Example 3 does not add methyl cellulose or sodium carboxymethyl cellulose, but replaces them with hydroxypropyl methyl cellulose. Compared with Examples 1-6, the thickness and porosity of the nickel electrode base tape obtained in Comparative Example 3 are lower than those in Comparative Example 1 and Comparative Example 2, and there are cracks on the surface. This shows that the use of the two binders of the present invention in combination can not only increase the thickness of the obtained nickel electrode base tape, but also improve the appearance quality of the nickel electrode base tape.

[0079] In addition, Example 4 changes the weight ratio of sodium carboxymethyl cellulose and methyl cellulose. Compared with Example 1, the thickness of the nickel electrode base tape obtained in Example 4 is reduced, and the porosity is reduced, indicating that the ratio of the two binders meets the preferred conditions and can further improve the thickness and porosity of the nickel electrode base tape. Example 5 changes the total amount of sodium carboxymethyl cellulose and methyl cellulose in the slurry, but the ratio of the two remains unchanged. Compared with Example 1, the thickness of the nickel electrode base tape obtained in Example 5 is reduced, and the porosity is reduced, indicating that the amount of the composite binder meets the preferred conditions and can further improve the thickness and porosity of the nickel electrode base tape. Example 6 uses nickel with different average particle sizes. Compared with Example 1, the thickness of the nickel electrode base tape obtained in Example 6 is reduced, and the porosity is reduced, indicating that the selection of nickel that meets the preferred conditions can further improve the thickness and porosity of the nickel electrode base tape.

[0080] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composition, characterized in that The composition comprises: nickel, a pore former, a binder 1 and a binder 2; wherein, The binder 1 is sodium carboxymethyl cellulose, and the binder 2 is methyl cellulose.

2. The composition according to claim 1, characterized in that In the composition, the weight ratio of the binder 1 to the binder 2 is (0.5-5.1):1; Preferably, in the composition, the weight ratio of the nickel to the pore-forming agent is (7-27):

1.

3. The composition according to claim 1 or 2, characterized in that The viscosity of a 1 wt % aqueous solution of the sodium carboxymethyl cellulose at 25° C. is greater than or equal to 500 mPa·s; Preferably, the viscosity of a 1 wt % aqueous solution of the methyl cellulose at 25° C. is 400-600 mPa·s.

4. The composition according to any one of claims 1 to 3, characterized in that The average particle size of the nickel is 2.1-2.8 μm, and the bulk density is 0.5-0.65 g / cm 3 ; Preferably, the pore former is selected from polyvinyl butyral and / or ammonium bicarbonate, preferably polyvinyl butyral; Preferably, the average particle size of the polyvinyl butyral is 100-500 μm; Preferably, the viscosity of a 10 wt % ethanol solution of the polyvinyl butyral at 25° C. is 5-10 mPa·s.

5. The composition according to any one of claims 1 to 4, characterized in that The composition also contains a solvent.

6. The composition according to claim 5, characterized in that The solvent is water; Preferably, the electrical conductivity of the solvent is less than or equal to 6.67 μS; Preferably, the content of the solvent in the composition is 50-60 wt %.

7. A nickel electrode substrate, characterized in that: The nickel electrode base tape is obtained by coating the composition according to claim 5 or 6 on at least one surface of a substrate, followed by drying and sintering; Preferably, the substrate is a nickel-plated steel strip.

8. The nickel electrode substrate according to claim 7, characterized in that: The sintering is carried out in the presence of protective gas and H2; Preferably, the sintering temperature is 900-1000°C and the sintering time is 5-30min; Preferably, the thickness of the nickel electrode base strip is greater than or equal to 1.2 mm, and the porosity is greater than 80%.

9. A nickel positive electrode battery, characterized in that: The nickel positive electrode battery comprises a nickel positive electrode, and the nickel positive electrode is made from the nickel electrode substrate according to claim 7 or 8.

10. Application of adhesive 1 and adhesive 2 in improving the thickness and surface quality of nickel electrode substrate; wherein, The binder 1 is sodium carboxymethyl cellulose, and the binder 2 is methyl cellulose.